RANCANG BANGUN SISTEM PENGINPUTAN DATA PENJUALAN ONLINE PADA PT. XYZ - Hesti Rian; Raihan Fathulhuda Ichwan (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to design and build an input system efficient and accurate online sales data for PT. XYZ. The method used in this research is the design method, and system development. This system is designed to make things easier online sales data input process with comprehensive features can improve the company's sales performance. Results of this research It is hoped that it can help PT. XYZ in improving efficiency and accuracy of inputting online sales data.